The Pembinaan tentang Apologetika Kristen dalam Menghadapi Isu-isu Kristologi di Gekesia Kota Manna Bengkulu Selatan - yosef, hery budi; Silaban, Guntur; Kansil, Dicky; Chandra, Iyan (STT Ebenhaezer Tanjung Enim, 2024)
Abstract This research is based on the widespread issues heard around the church, both inside and outside the church, related to Christology. The issue is increasingly growing because of the strong influence of social media witnessed by the masses, in this case the churches, especially in the Gekesia neighborhood in the Manna city area, South Bengkulu. Thus, all churches in the Inter-Church Cooperation Agency in South Bengkulu took the initiative to hold regular coaching to clarify Christian issues. The material that is our guidance is that the Church must be ready to face and